Venovenous extracorporeal membrane oxygenation (VV ECMO) in community-acquired pneumonia caused by Klebsiella pneumoniae. What went wrong? - Ślusarz, Krystian Adrian; Kurdyś, Paulina; Łanowy, Patrycja; Bichalski, Miłosz; Bijak, Bartosz; Trejnowska, Ewa (Journal of Education, Health and Sport, 2019)
Despite the progress that has been made in the field of medicine, severe hypoxic respiratory failure due to pneumonia has significant mortality. The etiology of pneumonia can be very different but possible complications include sepsis and acute respiratory distress syndrome (ARDS), resulting in patient’s increased risk of death. Severe respiratory failure in the course of ARDS, which does not respond to conventional therapy, is an indication for the implementation of venovenous extracorporeal membrane oxygenation support (VV ECMO). However, even with the use of targeted antibiotic therapy and advanced methods of extracorporeal life support, successful outcomes are not achieved. The location of the site of infection and the administration of targeted antibiotic therapy seem obvious to the patient’s prognosis. Antimicrobial therapy can only succeed if a few basic conditions are met. First of all, the right antibiotic should be used, given in the effective dose and as soon as possible after the onset of septic symptoms. In addition, the possibility of penetration of the active substance to the place affected by the inflammatory process also determines the probability of success of the therapy. This article presents a case report of Klebsiella pneumonia in a 38-year-old man and briefly discusses the challenges of modern medicine. In this case, the treatment was not successful, despite the known ethology, use of the targeted antibiotic therapy and advanced methods of extracorporeal life support. Further researches are needed to help improve treatment outcomes in this group, critically ill patients.